Al-Dharuriyah Al-Khamsah Dalam Perspektif Maqasid Syariah : Kerangka Pemikiran untuk Fikih Kontemporer - Sepmin Alfurqan; Lomba Sultan; Darussalam Syamsuddin (Madani: Jurnal Ilmiah Multidisiplin, 2026)
This study examines the role of al-daruriyyat al-khamsah within the framework of maqasid al-shariah as an analytical approach in contemporary Islamic legal thought. The objective of this research is to investigate the conceptual position of al-daruriyyat al-khamsah, analyze its function as a methodological framework in the process of legal derivation (istinbat), and explore its implications for the development of contemporary Islamic jurisprudence (fiqh). This research employs a qualitative method with a library research approach through normative-conceptual analysis of classical and contemporary Islamic legal literature. The findings indicate that al-daruriyyat al-khamsah—the preservation of religion, life, intellect, lineage, and property—constitute the core objectives of Islamic law and serve as fundamental parameters in legal reasoning. This concept is not merely theoretical but also functions as a practical instrument for evaluating legal rulings, balancing benefits (maslahah) and harms (mafsadah), and integrating textual evidence (nass) with contemporary realities. The study further demonstrates that a maqasid-based approach can enhance the adaptability of Islamic law in addressing modern issues such as economics, bioethics, governance, and environmental sustainability.The contribution of this research lies in strengthening maqasid al-shariah as a methodological framework within usul al-fiqh and offering an integrative approach to contemporary legal analysis that preserves the authenticity of divine revelation while remaining relevant to the challenges of the modern era.